Effects of dynamic aging on the wear and fracture strength of monolithic zirconia restorations - Işıl Sarıkaya; Yeliz Hayran (BMC, 2018)
Abstract Background The purpose of this study is to evaluate the wear and fracture strength of crowns and three-unit partial fixed dental prosthesis (FDP) fabricated using by Bruxzir and Incoris TZI as recently introduced monolithic zirconia materials. Methods A total of sixteen crowns and sixteen three-unit FDPs were fabricated using Bruxzir and Incoris TZI (n = 8). All specimens were subjected to a 2-body wear test in a dual axis chewing simulator for 1,200,000 loading cycles against steatite antagonist balls. The fracture strength and volumetric loss were recorded. The obtained data were statistically analyzed by 2-way ANOVA testing (α = 0.05). Results The mean volumetric loss of the crowns was higher than that of the three-unit FDPs (p < 0.05). Of the two monolithic systems, Incoris TZI exhibited more wear than Bruxzir. The fracture strengths of Bruxzir crowns and FDPs were found to be higher than those of the crowns and FDPs fabricated with Incoris TZI (p < 0.05). Conclusion In in vitro test conditions, Bruxzir and Incoris TZI monolithic zirconia systems are fracture-resistant for the crown and FDP application against physiologic chewing forces owing to dynamic aging. Among newly developed monolithic zirconia materials, Bruxzir is found to be more resistant to fracture compared to the Incoris TZI.